The SARAL/AltiKa mission: A step forward to the future of altimetry. Issue 2 (15th July 2021) - Verron, Jacques; Bonnefond, Pascal; Andersen, Ole; Ardhuin, Fabrice; Bergé-Nguyen, Muriel; Bhowmick, Suchandra; Blumstein, Denis; Boy, François; Brodeau, Laurent; Crétaux, Jean-François; Dabat, Mei Ling; Dibarboure, Gérald; et al.
Abstract: The CNES/ISRO altimetric satellite SARAL/AltiKa was launched in February 2013 and since then has provided useful data for various scientific and operational applications in oceanography, hydrology, cryospheric sciences and geodesy. However, a Reaction Wheel problem forced relaxation of the repeatability constraint on the satellite's orbit, which has been drifting slowly since July 2016. Beyond the expected contributions of this mission and its very good integration into the objectives of the constellation of altimetric satellites, it has become more and more apparent that specific contributions and innovations related to the main specification of SARAL/AltiKa, that is to say the use of the Ka-band, have clearly emerged. The advantages of the Ka-band are in short the reduction of ionosphere effects, the smaller footprint, the better horizontal resolution and the higher vertical resolution. A drawback of the Ka-band is the attenuation due to water/water vapor in case of rain and the resulting loss of data. The main objective of this paper is to highlight the specific advances of the Ka-band in different scientific and technical fields and to show why they are promising for the future and open the way to several missions or mission projects. Although unplanned initially, the fine coverage of the Drifting Phase brings some interesting openings especially for geodesy and hydrology applications.